The Impact of Problem Based Learning Model and Learning Motivation on Students' Poetry Writing Skills in Elementary School - Susanti, Nelly; Sukma , Elfia; Bentri , Alwen; Muhammadi, Muhammadi (Journal of Educational Sciences, 2025)
The goal of Indonesian language learning is for students to develop the ability to communicate effectively and efficiently in accordance with prevailing ethics, both orally and in writing. However, in this digital age, students have low language skills such as writing. The purpose of this study is to analyze the effect of the Problem Based Learning (PBL) model on the poetry writing ability of sixth-grade elementary school students. This research uses a quantitative research type with a quasi-experimental method. This study involved two schools as the experimental and control groups. The research instruments used are test questions and questionnaires. The research results show that the poetry text writing skills taught using the PBL model are higher than those taught using the conventional model. Second, the poetry text writing skills of highly motivated students taught using the PBL model are higher than those of highly motivated students taught using the conventional model. Third, the poetry text writing skills of low-motivated students are higher compared to students in the control class using the conventional learning model. Fourth, there is an interaction between the PBL learning model and students' learning motivation in influencing poetry text writing skills.